2017
DOI: 10.1371/journal.pone.0175760
|View full text |Cite
|
Sign up to set email alerts
|

Comparative molecular cytogenetic characterization of seven Deschampsia (Poaceae) species

Abstract: The genus Deschampsia P. Beauv (Poaceae) involves a group of widespread polymorphic species. Some of them are highly tolerant to stressful and variable environmental conditions, and D. antarctica is one of the only two vascular plants growing in Antarctic. This species is a source of useful for selection traits and a valuable model for studying an environmental stress tolerance in plants. Genome diversity and comparative chromosomal phylogeny within the genus have not been studied yet as karyotypes of most Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 52 publications
12
35
0
Order By: Relevance
“…14, A. aequalis, A. longiglumis, B. syzigachne and H. lanatus) and tetraploid (2n = 4x = 28, A. arundinaceus, A. latifolia and D. flexuosa) karyotypes with the typical for cereals basic chromosome number x = 7, except for the paleopolyploid D. cespitosa having 2n = 26 chromosomes. Our findings agreed with the cytological data reported earlier[36,37,62]. Particular, for D. cespitosa and some other Deschampsia species with 2n = 26, the analysis of meiotic chromosome behavior confirmed the basic number of chromosomes (n = 13) and also their diploid status[63].…”
supporting
confidence: 92%
See 3 more Smart Citations
“…14, A. aequalis, A. longiglumis, B. syzigachne and H. lanatus) and tetraploid (2n = 4x = 28, A. arundinaceus, A. latifolia and D. flexuosa) karyotypes with the typical for cereals basic chromosome number x = 7, except for the paleopolyploid D. cespitosa having 2n = 26 chromosomes. Our findings agreed with the cytological data reported earlier[36,37,62]. Particular, for D. cespitosa and some other Deschampsia species with 2n = 26, the analysis of meiotic chromosome behavior confirmed the basic number of chromosomes (n = 13) and also their diploid status[63].…”
supporting
confidence: 92%
“…Chromosome staining with DAPI performed after FISH/GISH procedures revealed DAPI-banding patterns specific to the studied species accessions. Large chromosomes, etc,) are especially common [27,37], and this karyotype diversity is considered to be related to the plasticity of plant genomes [60,61]. Despite the stressful natural environmental conditions, the cytogenetic analysis showed that the studied accessions presented normal diploid (2n [37,62,65].…”
Section: Dapi-banding Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the species from both Deschampsia and Holcus contain common DNA repeats CON1, CON2, COM1 and COM2 which are widespread in Poaceae [15]. parvula [37]. According to the phylogenetic analyses inferred from nuclear ITS and plastid trnL sequence data, D. flexuosa is regarded a better suited to the genus Avenella [78].…”
Section: Dapi-banding Analysismentioning
confidence: 99%